THE INFLUENCE OF TAX SOCIALIZATION, TAX SANCTIONS, UNDERSTANDING OF TAX REGULATIONS AND TAX AWARENESS REGARDING TAXPAYER COMPLIANCE IN SURABAYA - Widya Indah Nurmalasari (Politeknik Ubaya, 2023)
Tax is an obligation that must be carried out by every community as a taxpayer to meet state expenditure needs to improve people's welfare. However, there are still many taxpayers who are not aware of their tax compliance. So the aim of this research is to analyze the impact of Tax Socialization, Tax Sanctions, Understanding of Tax Regulations, and Tax Awareness on Taxpayer Compliance. The type of study is quantitative. The population was 100 Taxpayers by getting the sample using the Total Sampling method so that the sample size was 100 respondents Taxpayer in Surabaya. Research data includes primary data from distributing questionnaires and secondary data from the literature. The data analysis technique uses the SEM Partial Least Square test. The research results prove that Tax Sanctions and Tax Awareness have a significant positive impact on Taxpayer Compliance. Then, Tax Socialization and Understanding of Tax Regulations do not have a significant impact on Taxpayer Compliance in Surabaya.